Observation, replication, and measurement in sports economics - Fort, R. (Journal of Sports Economics, 2009)
This paper provides an introduction to the special edition as well as my contribution on the topics covered in this special edition—observation, replication, and measurement issues relevant to sports economists. The papers cover issues related to the professional conveyance of first-hand experience, interaction with related sports analysis communities not governed by peer review or our usual citation requirements, data integrity, data and result replication, and second-hand measurement relevant to particular economic questions. My contribution is in brief descriptions concerning how these issues have intruded on some of my own work.